Transition to Kindergarten: Negative Associations between the Emotional Availability in Mother–Child Relationships and Elevated Cortisol Levels in Children with an Immigrant Background - Rickmeyer, Constanze; Lebiger-Vogel, Judith; Leuzinger-Bohleber, Marianne (Frontiers in Psychology, 2017)
Background: The transition to child care is a challenging time in a child’s life and leads to elevated levels of cortisol. These elevations may be influenced by the quality of the mother-child-relationship. However, remarkably little is known about cortisol production in response to the beginning of child care among children-at-risk such as children with an immigrant background. However, attending kindergarten or any other child day-care institution can for example have a compensating effect on potential language deficits thus improving the educational opportunities of these children. Method: Data of a subsample of N = 24 “hard-to-reach” mother-child dyads was collected in the context of the psychoanalytic early prevention project “First Steps”. The project focuses on the earliest integration of children with an immigrant background by supporting parenting capacities in the critical phase of migration and early parenthood. Children’s hair cortisol concentration (HCC) was assessed one week before (mean age = 38.77 months) and three months after kindergarten entry (mean age = 42.26 months). Hair analysis was conducted for both times of measurement, reflecting the first 3 months after kindergarten entry and 3 months prior. Furthermore, the emotional quality of the mother-child-relationship was assessed with the help of the Emotional Availability Scales (EAS) shortly before kindergarten entry when the children were about three years old (mean age = 37.2). Results and Conclusion: Children’s mean cumulated HCC was higher after kindergarten entry than before. The increase correlated negatively with several dimensions of the EAS. Repeated measures ANCOVA revealed that particularly responsive children and children who had experienced less intrusive mother-child-relationships demonstrated lower elevations in HCC after kindergarten entry. Furthermore, a decreased EA score was found in all EA dimensions, besides the dimension “mother’s non-hostility”, indicating problematic EA within the mother-child-relationships of the sample. The results suggest that children with an immigrant background who experience more emotional available mother-child-relationships seem to regulate stress induced by kindergarten entry more effectively, indicated by lower cortisol elevations after entry. This implicates that supporting early mother-child-relationships by intervention may have a positive effect on the children’s ability to regulate stress induced by kindergarten entry thus promoting child development.